Essential Trace Elements in Patients with Dyslipidemia: A Meta-analysis - Li, Cui-Ping; Song, Yu-Xin; Lin, Zi-Jun; Ma, Mei-Lin; He, Lian-Ping (Current Medicinal Chemistry, 2024)
Background: Lipid metabolism is a complex process that includes lipid uptake, transport, synthesis, and degradation. Trace elements are vital in maintaining normal lipid metabolism in the human body. This study explores the relationship between serum trace elements and lipid metabolism. Methods: In this study, we reviewed articles on the relationship between alterations in somatic levels of zinc, iron, calcium, copper, chrome, manganese, selenium, and lipid metabolism. In this systematic review and mate-analysis, databases such as PubMed, Web of Science, and China National Knowledge Infrastructure (CNKI), Wanfang was searched for articles on the relationship published between January 1, 1900, and July 12, 2022. The meta-analysis was performed using Review Manager5.3 (Cochrane Collaboration). Results: No significant association was found between serum zinc and dyslipidemia, while other serum trace elements (iron, selenium, copper, chromium, and manganese) were associated with hyperlipidemia. Conclusion: The present study suggested that the human body's zinc, copper, and calcium content may be related to lipid metabolism. However, findings on lipid metabolism and Iron, Manganese have not been conclusive. In addition, the relationship between lipid metabolism disorders and selenium levels still needs to be further studied. Further research is needed on treating lipid metabolism diseases by changing trace elements.
Keywords: cadmium